Clinical Value of Surveillance Biopsies in Pediatric Liver Transplantation. Issue 5 (20th January 2022) - Rocque, Brittany; Zaldana, Aaron; Weaver, Carly; Huang, Julia; Barbetta, Arianna; Shakhin, Victoria; Goldbeck, Cameron; Yanni, George; Zielsdorf, Shannon; Kwon, Yong; Etesami, Kambiz; Genyk, Yuri; et al.
Abstract : Although pediatric liver transplantation (LT) results in excellent long‐term outcomes, a high incidence of early acute cellular rejection and late graft fibrosis persists. Routine measurement of allograft enzymes may not reliably detect rejection episodes, identify candidates for immunosuppression minimization, or indicate allograft fibrosis. Surveillance biopsies (SBs) can provide valuable information in this regard, but their role in pediatric LT is not fully established. A retrospective cohort of 236 pediatric LT recipients from a high‐volume center was studied to characterize the risks and benefits of SB versus for‐cause biopsies (FCBs). The study population was 47.1% male and 54.7% Hispanic, and 31% received living donor grafts. Our data suggest that patients in the SB group had better transplant outcomes (rejection‐free, graft, and patient survival) compared with patients who had FCBs or who never underwent biopsy. Among 817 biopsies obtained from 236 patients, 150 (18.4%) were SBs. Only 6 patients had a biopsy‐related complication, and none were observed in the SB subset. Graft biochemical blood tests did not accurately predict rejection severity on biopsy, with aspartate aminotransferase area under the receiver operating characteristic curve (AUROC) 0.66, alanine aminotransferase AUROC 0.65 (very poor predictions), and gamma‐glutamyltransferase AUROC 0.58 (no prediction). SBs identified subclinical rejection in 18.6% of biopsies, whereas 63.3% of SBs had evidence of fibrosis. SBs prompted changes in immunosuppression including dose reduction. Our experience suggests that SB in pediatric LT is safe, offers valuable information about subclinical rejection episodes, and can guide management of immunosuppression, including minimization. Improved outcomes with SB were likely multifactorial, potentially relating to a more favorable early posttransplant course and possible effect of management optimization through SB. Further multicenter studies are needed to examine the role of SBs on long‐term outcomes in pediatric LT.